2020
DOI: 10.1007/s12144-020-01148-7
|View full text |Cite
|
Sign up to set email alerts
|

The differential mental health impact of COVID-19 in Arab countries

Abstract: COVID-19 pandemic’s mental health impact on Arab countries is under-researched. The goal of this investigation was to study the differential impact of COVID-19 on the mental health of Arab countries. A questionnaire including measures of COVID-19 traumatic stress, PTSD, depression, anxiety, and cumulative stressors and trauma was distributed anonymously online in seven Arab countries (Egypt ( N = 255), Kuwait ( N = 442), Jordan ( N = 216), Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
2
34
1
Order By: Relevance
“…In contrast to this study, results from a study conducted in the United States indicated that being a sophomore, a senior or a junior was associated with higher anxiety levels compared to Freshmen ( Kecojevic et al., 2020 ). Family income in our study has no association with anxiety (p = 0.178), however, in a study conducted among several Arab countries, income was a significant predictor of lower levels of anxiety in individuals from higher-income countries such as Kuwait and Saudi Arabia ( Shuwiekh et al., 2020 ).…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to this study, results from a study conducted in the United States indicated that being a sophomore, a senior or a junior was associated with higher anxiety levels compared to Freshmen ( Kecojevic et al., 2020 ). Family income in our study has no association with anxiety (p = 0.178), however, in a study conducted among several Arab countries, income was a significant predictor of lower levels of anxiety in individuals from higher-income countries such as Kuwait and Saudi Arabia ( Shuwiekh et al., 2020 ).…”
Section: Discussioncontrasting
confidence: 79%
“…In conclusion, our results are in line with the research on the psychological impact caused by the present pandemic on the general population (Alzueta et al, 2021;Ferrucci et al, 2020;Koçak et al, 2021;Shah et al, 2021;Shuwiekh et al, 2020), as well as with that on a specific category of workers like HCPs (Eftekhar-Ardebili et al, 2021;Felice et al, 2020;Giusti et al, 2020;Lai et al, 2020;Orrù et al, 2021;Palacios-Ceña et al, 2020;Rossi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The literature also posits job insecurity as a proxy through which external factors can affect other attitudinal and behavioural variables (Mahmoud & Reisel, 2015). Further, the most recent studies investigating COVID-19 psychological effects (e.g., Shuwiekh et al, 2020) have not extensively covered the MENA region. Thus, we expect that COVID-19 perceptions effects will be transmitted via job insecurity into burnout.…”
Section: Job Insecuritymentioning
confidence: 99%